The Role of Artificial Intelligence in Preserving Cultural Heritage (Al-Jabal Journal of Humanities and Applied Sciences, 2024)
The present era is witnessing significant progress in the field of artificial intelligence,which has affected all fields, including the field of cultural heritage.This research aims to highlight the methods of using artificial intelligence in protecting and conserving  cultural heritage as well as its contribution to promote and identify it.Additionally, Algeria's experience in this field and the challenges it has faced were also addressed.
Keywords: Cultural heritage, modern technologies, artificial intelligence, conservation, protection